1979
DOI: 10.1017/s0022215100088162
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in perforations of the tympanic membrane

Abstract: 70 patients with dry central perforations have been studied to assess the hearing loss. The hearing loss is greater at the lower frequencies and increases with the size of the perforation. Malleolar perforations cause more hearing loss than the non-malleolar unless the perforation involves less than 10 per cent of the tympanic membrane surface area. Perforations of the postero-inferior quadrant cause more hearing loss than those in the antero-inferior quadrant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
51
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 5 publications
(4 reference statements)
11
51
3
3
Order By: Relevance
“…A postero-inferior perforation results in larger hearing loss than an antero-inferior perforation. Ahmad and Ramani [6] had also found similar findings in their study where they found 18.5 dB HL in anterior perforation and 29 dB HL in posterior perforation with 500 Hz. But they concluded: ''It is seen that the difference in hearing losses between antero and postero-inferior perforations, is appreciable only at the lower frequencies''.…”
Section: Discussionsupporting
confidence: 74%
“…A postero-inferior perforation results in larger hearing loss than an antero-inferior perforation. Ahmad and Ramani [6] had also found similar findings in their study where they found 18.5 dB HL in anterior perforation and 29 dB HL in posterior perforation with 500 Hz. But they concluded: ''It is seen that the difference in hearing losses between antero and postero-inferior perforations, is appreciable only at the lower frequencies''.…”
Section: Discussionsupporting
confidence: 74%
“…Posteroinferior perforations abolish the sound protection of the round window and hence, they will cause more hearing loss than perforations in other quadrant. 9 To sum up, because of the high incidence of conductive hearing loss caused by central perforations of tympanic membrane, the conflicting reports regarding the effect of perforations on hearing loss, this project has been under taken to study the effects of site and size of tympanic membrane perforation on degree of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in energy transfer efficiency caused by TM perforation has been measured in human temporal bones and simulated in a simple circuit model by Voss et al ͑2001a;2001b;2001c; with a series of publications. It has been tested in animals ͑Bigelow et al, 1996;Santa Maria et al, 2007͒ andclinical studies ͑Ahmad andRamani, 1979;Mehta et al, 2006͒. However, the circuit model does not have structural geometry, and the parameters of the model are determined by fitting model results with experimental a͒ Author to whom correspondence should be addressed. Electronic mail: rgan@ou.edu b͒ Present address: Massachusetts Eye and Ear Infirmary, Harvard Medical School, Boston, MA 02114. measurements in each individual temporal bone.…”
Section: Introductionmentioning
confidence: 99%